Strategic option pricing - Volker Bieta; Udo Broll; Wilfried Siebe (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2020)
In this paper an extension of the well-known binomial approach to option pricing is presented. The classical question is: What is the price of an option on the risky asset? The traditional answer is obtained with the help of a replicating portfolio by ruling out arbitrage. Instead a two-person game from the Nash equilibrium of which the option price can be derived is formulated. Consequently both the underlying asset's price at expiration and the price of the option on this asset are endogenously determined. The option price derived this way turns out, however, to be identical to the classical no-arbitrage option price of the binomial model if the expiration-date prices of the underlying asset and the corresponding risk-neutral probability are properly adjusted according to the Nash equilibrium data of the game.
urn:nbn:de:bsz:14-qucosa2-717192
Keywords: G12; G13; C72; 330; option pricing; game theory; Nash equilibrium